Development Of An Effective Tax Obligation Socialization Method For Msme Business Actors Based On Game Concepts - Arda, Devid Putra; Chandra, Hendra (SEAN Institute, 2024)
The awareness level of taxpayers among business operators in the MSME sector is still perceived as low. The main factor contributing to this is the lack of understanding of their obligations as tax subjects and objects, as well as not realizing that there are penalties for non-compliance with regulations. Therefore, intensive outreach needs to be conducted, equipped with attractive and non-boring educational tools based on games (EduGames). The research method used is a qualitative method with a participatory approach involving MSME operators. Through a participatory approach, MSME operators can provide input and participate in the decision-making process. This study also uses an experimental method with a quasi-experimental approach. The subjects of the study are 25 MSME operators, primarily focusing on siomay and dim sum businesses, operating in Kembangan District, Meruya Selatan Subdistrict, West Jakarta. The results of this study can conclude the following points: (1) Most MSME operators do not understand the applicable tax regulations, let alone the latest tax regulations; (2) Tax payment awareness is still low because they believe that tax obligations are only imposed on large-scale businesses; (3) The concept of interactive games (EduGames) is very helpful in providing an understanding of tax regulations and laws; (4) The implication of using the tax obligation outreach method based on the game concept (EduGames) for improving tax compliance is highly effective, as proven by the increased understanding of participants after engaging in the game compared to before.